The impact of renewable energy on job growth in South Africa - Van der Westhuizen, Johann Vincent (School of Economics, 2026)
The threat of climate change and the consequent need for renewable energy development is an issue of growing importance across the world. While the environmental benefits of renewable energy are commonly documented and accepted, the economic impact of renewables on job growth is less commonly agreed upon. For South Africa in particular, the nature of this impact is crucial to understand since the country suffers from both unsustainable carbon emissions and unemployment rates. This study investigates the impact of renewable energy consumption on total employment in South Africa over the period 1970-2021. The autoregressive distributed lag model was employed to test the long-run and short-run impacts of renewable energy consumption on employment in a multivariate framework including other determinants of labour demand. Our findings indicate that renewable energy consumption does not have any significant statistical impact on total employment. Additionally, our findings indicate the importance of economic growth, human capital levels, foreign direct investment, energy consumption and international trade in determining job growth. Therefore, the study advocates for further research into the determinants of labour demand in South Africa, and the active creation of a positive relationship between renewable energy and job growth given the current low carbon energy transition that is taking place in South Africa.